In silico simulation of blood glucose-insulin dynamics using MATLAB-Simulink - Abdul Malik, Muhammad Iqbal; Mahmud, Farhanahani; Masdar, Aizan (Penerbit UTHM, 2020)
Diabetes mellitus (DM) is a major public health concern in Malaysia and it continuously increases over years. Based on International Diabetes Federation, there are rising numbers of people having diabetes with 3.6 million people in Malaysia and 463 million people in the world [1]. The National Health and Morbidity Survey (NHMS) 2019 has shown that the diabetes in Malaysia has increased from 13.4% in 2015 to 18.3% in 2019 [2]. This can significantly increase the cost in diabetes treatment and management.